Late Presentation of Uterine Rupture Following Vaginal Birth After Cesarean Delivery: A Case Report - Lindsey A. Choi; Ariel A. Chung; Brian Pierce (Thieme Medical Publishers, Inc., 2020)
Background A trial of labor after cesarean delivery is associated with uterine rupture rates of 0.5 to 0.9%, which can have devastating neonatal and maternal consequences. While uterine rupture typically occurs during labor, it can clinically manifest after delivery. Case A 23-year-old multiparous female presented in labor at term. Her obstetrical history was significant for a prior low transverse cesarean delivery. She had an uncomplicated labor course and spontaneous vaginal delivery. Immediately after delivery, she complained of severe right shoulder and left lower quadrant pain. Bedside ultrasound revealed a 10-cm, complex, adnexal mass adjacent to the uterus without free fluid. She was hemodynamically stable and appeared clinically well. On repeat ultrasound, the mass was unchanged; however, the patient now had free intraperitoneal fluid along the liver edge. Emergent laparotomy revealed a uterine rupture along her prior hysterotomy with extension into the right uterine artery. A 10-cm broad ligament hematoma ruptured posteriorly resulting in a 1-L hemoperitoneum. She received multiple blood products intraoperatively and recovered well postpartum. Conclusion Delivery after trial of labor after cesarean delivery usually decreases acuity; however, these patients remain at risk for significant complications. Clinicians should continue to assess patients in the immediate postpartum period and proceed with surgical intervention if necessary.